OPTIMALISASI PENERAPAN PEDOMAN INTERPRETASI STANDAR AKUNTANSI KEUANGAN (ISAK) NO 35 PADA LAPORAN KEUANGAN MASJID AL-IKHLAS BLURU PERMAI SIDOARJO - Wadhah, Ambar Nabilah; Rahayu, Dewi Sri; Anwar, Chairil (Jurnal Akuntansi Syariah (JAkSya), 2024)
Optimizing the Financial Accounting Standards Interpretation (ISAK) No.35 guidelines is very important for mosque non-profit organizations to ensure accountability and transparency in financial management. This research aims to collect financial reports for the Al-Ikhlas Bluru Permai Sidoarjo Mosque adjusted to ISAK 35. The method used is qualitative description through observation, documentation and interviews. The results of the research state that the mosque's financial reports only record receipts and expenditures, so they do not meet ISAK 35 standards. Financial recording is only carried out if there is cash in and cash out (cash basis). Then the amount of money coming in, money going out, and the amount of cash is reported every Friday by conveying it through the mosque's microphone. It is recommended that mosque administrators increase their understanding of non-profit accounting standards and implement a comprehensive accounting cycle to improve transparency and accountability in fund management. By implementing ISAK 35, it is hoped that mosques can prepare financial reports that are more comprehensive, accurate and in accordance with ISAK guidelines, so that public confidence in the management of mosque funds increases. The importance of transparent and accurate financial reports is not only for internal accountability but also to maintain the trust of donors and the wider community.Keywords: Accountability; Financial Reports; ISAK 35; Mosque; Non-Profit┬áOptimalisasi penerapan pedoman Interprestasi Standar Akuntansi Keuangan (ISAK) No.35 sangat penting bagi organisasi nirlaba masjid untuk memastikan akuntabilitas dan transparansi dalam pengelolaan keuangan. Penelitian ini bertujuan mengevaluasi laporan keuangan Masjid Al-Ikhlas Bluru Permai Sidoarjo disesuaikan dengan ISAK 35. Metode yang digunakan deskripsi kualitatif melalui observasi, dokumentasi, dan wawancara. Hasil penelitian menyatakan bahwa laporan keuangan masjid hanya mencatat penerimaan dan pengeluaran, sehingga tidak memenuhi standar ISAK 35. Pencatatan keuangan hanya dilakukan apabila terdapat kas masuk dan kas keluar (cash basis). Kemudian jumlah uang masuk, uang keluar, dan jumlah uang tunai dilaporkan setiap hari Jumat dengan disampaikan melalui microphone masjid. Disarankan agar pengurus masjid meningkatkan pemahaman tentang standar akuntansi nirlaba dan menerapkan siklus akuntansi secara menyeluruh untuk memperbaiki transparansi dan akuntabilitas pengelolaan dana. Dengan penerapan ISAK 35, diharapkan masjid dapat menyusun laporan keuangan yang lebih komprehensif, akurat, dan sesuai pedoman ISAK, sehingga kepercayaan masyarakat terhadap pengelolaan dana masjid meningkat. Pentingnya laporan keuangan yang transparan dan akurat tidak hanya untuk akuntabilitas internal tetapi juga untuk menjaga kepercayaan para donatur dan masyarakat luas.Kata Kunci: Akuntabilitas; ISAK 35; Laporan keuangan; Masjid; Nirlaba